Tinjauan Hukum Islam terhadap Kewarisan Kelem pada Masyarakat Kecicang Islam - Umam, Ijtihadul (ISLAMITSCH FAMILIERECHT JOURNAL, 2021)
Kelem hereditary is one of the customary laws in the matter of the inheritance rights of grandchildren which is the result of the agreement of former community leaders in Kecicang Islam Village, Bungaya Kangin Village, Bebandem District, Karangasem Regency, Bali Province. Kelem comes from the Balinese language which means drowned. In terms of hereditary, kewarisan kelem means a grandson whose father or mother (the heir) died before the grandfather or grandmother (the inheritor) is said to have drowned (blocked) from inheritance rights because it is hindered by the parents’ brothers who are still alive. This is in contrast to the hereditary law system in Indonesia in the form of Islamic Law Compilation article 185 paragraph 1, which explains that, the heir who dies before the inheritors can be replaced by his child. The research method used was field research. This research was a descriptive analytic with juridical normative approach. Data collection methods used include interviews and documentation. After the data was collected, it was analyzed in a descriptive qualitative way with the 'urf and the theory of substitute heirs. The results showed that kelem hereditary is one of the customary laws as the result of the agreement of former community leaders in Kecicang Islam. This contradicts both Sunni and Shi'ah hereditary law systems as well as the hereditary laws in Indonesia.